Traducción del texto "New classification of endometrial cancers: the development and potential applications of genomic-based classification in research and clinical care" - Alvarez, Gabriela Fernanda (2025)
Fil: Alvarez, Gabriela Fernanda. Universidad Nacional de Córdoba. Facultad de Lenguas; Argentina.